MODERN APPROACHES TO SURGICAL TREATMENT OF INFERIOR ORBITAL WALL FRACTURES (Modern education and development, 2025)
This study presents a summary of our clinical experience in the surgical rehabilitation of patients with inferior orbital wall fractures. A comprehensive clinical and radiological examination was conducted both preoperatively and postoperatively in 14 patients diagnosed with orbital floor injuries. These fractures were observed both in isolated cases and in combination with zygomatic-orbital complex fractures. Analysis of the cases revealed that isolated inferior orbital wall fractures accounted for 57.14% of the total, with the predominant patient group being young males (78.57%).During surgical treatment, a transantral approach was utilized in all cases, providing optimal access to the inferior orbital wall. In instances where the orbital floor fracture was associated with a zygomatic-orbital complex injury, not only was the orbital floor repositioned, but the zygomatic complex was also stabilized at three standard anatomical fixation points. In cases of isolated injury, characteristic of the so-called pure “blow-out” fracture, the technique of bone-plastic antrotomy was employed as a variation of the transantral approach, allowing for the prevention of a defect in the anterior wall of the maxillary sinus.For osteosynthesis, titanium materials were used in all clinical cases, including F-shaped miniplates or individually contoured titanium meshes, particularly in cases of significant bone defects. As a result of the surgical intervention, all patients achieved restoration of both functional and aesthetic parameters disrupted by the trauma. Long-term outcomes demonstrated complete recovery of binocular vision and the absence of enophthalmos, confirming the high efficacy of the proposed approach.